Genetic variation in neuropeptide Y interacts with childhood trauma to influence anxiety sensitivity. Issue 4 (4th July 2021) - Womersley, Jacqueline Samantha; Martin, Lindi; van der Merwe, Lize; Seedat, Soraya; Hemmings, Sian Megan Joanna
ABSTRACT: Background and objectives: Anxiety sensitivity (AS) refers to a fear of the negative implications of anxiety, and arises due to gene-environment interactions. We investigated whether genetic variation in two neuropeptides implicated in the stress response, neuropeptide Y (NPY) and pituitary adenylate cyclase-activating polypeptide receptor 1, interacted with childhood trauma (CT) to influence AS. Design and methods: This cross-sectional study examined the CT x genetic variant effects on AS in 951 adolescents who self-identified as Xhosa or South African Colored (SAC) ethnicity. Results: In Xhosa females, the NPY rs5573 A allele and rs3037354 deletion variant were associated with increased ( p = 0.035) and decreased ( p = 0.034) AS, respectively. The interaction of CT and the NPY rs5574 A allele increased AS in SAC female participants ( p = 0.043). The rs3037354 deletion variant protected against AS with increased CT in SAC male participants ( p = 0.011). Conclusions: The NPY rs5574 A allele and rs3037354 deletion variant interact with CT to act as risk and protective factors, respectively, for AS in an ethnicity- and sex- differentiated manner. Our results reaffirm the role of NPY and gene-environment interactions in anxiety-related behaviors and reinforce the need for psychiatric genetics studies in diverse populations.